QUALITY DESIGN OF BATIK TULIS USING THE TAGUCHI METHOD - Purnomo Hari, Lutfianto Saufik & Apsari Ayudyah Eka (International Journal of Research Science and Management, 2018)
In the batik industry center of Pemalang, a lack of product quality standards have led to complaints from consumers who do not like the batik products. Products that have been purchased by consumers are returned because of inferior quality. From the initial survey about batik conducted with 30 respondents in Pemalang, it was found that 80% of respondents chose Pekalongan batik rather than Pemalang batik. This is due to customers complaining about the wearing of colors and the use of non-sturdy and uncomfortable materials. The purpose of this study was to determine the characteristics needed for optimal batik product design. The method used was a pure experimental design using the Taguchi method with orthogonal array L27(313). The results of this study suggest that the optimal characteristics of batik are primissima butterfly cloth, coloring using naftol, dyeing for 50 minutes and the process of waxing with a temperature of 700C. The optimum level setting provided a quality enhanced by 1.78 grey scale or 22.22%